STUDENTS LEARNING OUTCOMES DIFFERENCES ON AKIDAH AKHLAK: A STUDY OF COOPERATIVE LEARNING MODELS ON JIGSAW-TYPE AND STAD-TYPE OF KALAM SCIENCE MAIN TOPIC AT CLASS XI IN MADRASAH ALIYAH NEGERI 1 POLEWALI MANDAR - Mustamin, Mustamin; Ismail, Ilyas; Ismail, Wahyuni (Program Pascasarjana, UIN Alauddin Makassar, 2022)
This study examines the learning outcomes of students in moral academia subjects using jigsaw and STAD-type cooperative learning models in MAN 1 Polewali Mandar. This research is a pseudo-experiment. The samples were class XI IPA 1 and class XI IPS 2, both given treatment (treatment). Class XI IPA 1 was given the treatment of the jigsaw-type cooperative learning model, and class XI social studies two was given the treatment of STAD type cooperative learning model. In data collection, researchers used tests, observations, and documentation. The data obtained were then processed using an independent test formula of the t-test sample, with the help of the SPSS version 25 application. The results of the study obtained in the two groups through descriptive statistical analysis, the average learning outcomes of akidah akhlak using the jigsaw type learning model were = 81.25. In contrast, the average learning outcomes of Akidah akhlak using the STAD-type cooperative learning model were = 79.60. The results of the data homogeneity analysis showed that the F-value = 1.343 ≤ Ftabel = 4.10 expressed the sample data as homogeneous. For the Hypothesis test, the t-test showed that what was obtained was calculated as 1.76 < table 1.991, this shows that H0 is accepted and H1 is rejected, so it can be concluded that there is no difference in learning outcomes in classes taught with the jigsaw-type and the STAD-type cooperative-learning model class XI science one and class XI IPS 2 in MAN 1 Polewali Mandar.